Role of Prophylactic Dimenhydrinate Versus Ondansetron as an Adjunct to Dexamethasone on Post-Operative Nausea and Vomiting in Laparoscopic Abdominal Procedures - Aaifa Khalid Niazi; Sadaf Bukhari; Syed Mahmood Ali; Maria Arshad; Muhammad Taqi (Proceedings, 2020)
Introduction: Post-operative nausea and vomiting (PONV) is a common complication in patients undergoing surgery. Anti-emetic prophylaxis is recommended for all high risk patients. Combination therapy is considered superior to single dose prophylaxis however its efficacy in varied laparoscopic abdominal surgical situations has not been investigated.